CYP1B1 as a therapeutic target in cardio-oncology - Carrera, Alexa N. (Clin Sci (Lond), 2020)
Cardiovascular complications have been frequently reported in cancer patients and survivors, mainly because of various cardiotoxic cancer treatments. Despite the known cardiovascular toxic effects of these treatments, they are still clinically used because of their effectiveness as anti-cancer agents. In this review, we discuss the growing body of evidence suggesting that inhibition of the cytochrome P450 1B1 enzyme (CYP1B1) can be a promising therapeutic strategy that has the potential to prevent cancer treatment-induced cardiovascular complications without reducing their anti-cancer effects. CYP1B1 is an extrahepatic enzyme that is expressed in cardiovascular tissues and overexpressed in different types of cancers. A growing body of evidence is demonstrating a detrimental role of CYP1B1 in both cardiovascular diseases and cancer, via perturbed metabolism of endogenous compounds, production of carcinogenic metabolites, DNA adduct formation, and generation of reactive oxygen species (ROS). Several chemotherapeutic agents have been shown to induce CYP1B1 in cardiovascular and cancer cells, possibly via activating the Aryl hydrocarbon Receptor (AhR), ROS generation, and inflammatory cytokines. Induction of CYP1B1 is detrimental in many ways. First, it can induce or exacerbate cancer treatment-induced cardiovascular complications. Second, it may lead to significant chemo/radio-resistance, undermining both the safety and effectiveness of cancer treatments. Therefore, numerous preclinical studies demonstrate that inhibition of CYP1B1 protects against chemotherapy-induced cardiotoxicity and prevents chemo- and radio-resistance. Most of these studies have utilized phytochemicals to inhibit CYP1B1. Since phytochemicals have multiple targets, future studies are needed to discern the specific contribution of CYP1B1 to the cardioprotective and chemo/radio-sensitizing effects of these phytochemicals.